Myocardial edema during chemotherapy for gynecologic malignancies: A cardiac magnetic resonance T2 mapping study - Yang, Meng-Xi; Li, Qing-Li; Wang, Dan-Qing; Ye, Lu; Li, Ke-Min; Lin, Xiao-Juan; Li, Xue-Sheng; Fu, Chuan; Ma, Xin-Mao; Liu, Xi; Yin, Ru-Tie; Yang, Zhi-Gang; et al. (Frontiers in Oncology, 2022)
Objective Myocardial edema is an early manifestation of chemotherapy-related myocardial injury. In this study, we used cardiac magnetic resonance (CMR) T2 mapping to assess myocardial edema and its changes during chemotherapy for gynecologic malignancies. Methods We enrolled 73 patients receiving chemotherapy for gynecologic malignancies, whose the latest cycle was within one month before the beginning of this study, and 41 healthy volunteers. All participants underwent CMR imaging. Of the 73 patients, 35 completed CMR follow-up after a median interval of 6 (3.3 to 9.6) months. The CMR sequences included cardiac cine, T2 mapping, and late gadolinium enhancement. Results Myocardial T2 was elevated in patients who were treated with chemotherapy compared with healthy volunteers [41ms (40ms to 43ms) vs. 41ms (39ms to 41ms), P = 0.030]. During follow-up, myocardial T2 rose further [40ms (39ms to 42ms) vs. 42.70 ± 2.92ms, P < 0.001]. Multivariate analysis showed that the number of chemotherapy cycles was associated with myocardial T2 elevation (β = 0.204, P = 0.029). After adjustment for other confounders, myocardial T2 elevation was independently associated with a decrease in left ventricular mass (β = −0.186; P = 0.024). Conclusion In patients with gynecologic malignancies, myocardial edema developed with chemotherapy cycles increase, and was associated with left ventricular mass decrease. T2 mapping allows the assessment of myocardial edema and monitoring of its change during chemotherapy.